2014
DOI: 10.1111/joa.12252
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of matching symmetry in the human pinnae with possible implications for 3D ear recognition and sound localization

Abstract: The human external ears, or pinnae, have an intriguing shape and, like most parts of the human external body, bilateral symmetry is observed between left and right. It is a well-known part of our auditory sensory system and mediates the spatial localization of incoming sounds in 3D from monaural cues due to its shape-specific filtering as well as binaural cues due to the paired bilateral locations of the left and right ears. Another less broadly appreciated aspect of the human pinna shape is its uniqueness fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…Because the coordinates of the landmarks serve as variables in the subsequent analyses, it is important that each variable is a coordinate of the same point for all the specimens in the sample. This correspondence of landmarks, or homology in the context of comparative evolutionary studies, is a central assumption of geometric morphometric methods [9], even for semilandmarks and similar methods that use points selected along a smooth outline or surface [104,[202][203][204][205]. Because fluctuating asymmetry is usually investigated within populations and the scale of variation is normally relatively small, correspondence of landmarks tends to be a less serious problem than in studies of evolutionary or ontogenetic variation.…”
Section: Landmarks Procrustes Methods and Shape Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Shape asymmetry, involving either matching symmetry or object symmetry [24][25][26] can be estimated from landmarks or semi-landmarks in either two or three dimensions [25][26][27][28][29][30][31][32], as well as continuous symmetry measures [12,[33][34][35]. Despite the apparent simplicity of fluctuating asymmetry, careless researchers can easily reach erroneous conclusions [8,12,22,23,36].…”
Section: Measuring Fluctuating Asymmetrymentioning
confidence: 99%